Anastomotic leakage is associated with impaired overall and disease-free survival after curative rectal cancer resection: a propensity score analysis - Kulu, Yakup; Tarantio, Ignazio; Warschkow, Rene; Kny, Sandra; Schneider, Martin; Schmied, Bruno M.; Büchler, Markus W.; Ulrich, Alexis (Annals of surgical oncology, 2015)
Whether anastomotic leakage (AL) has a negative impact on survival remains a matter of debate. This study aimed to assess the impact of AL on the overall and disease-free survival of patients undergoing curative resection of stages 1-3 rectal cancer using propensity-scoring methods.